2021
DOI: 10.2147/ijn.s287415
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Theranostic Effect: Conjugation of Photothermal and Photodynamic Therapies Based on an in vivo Demonstration

Abstract: Introduction: Cancer is the second leading cause of death globally and is responsible, where about 1 in 6 deaths in the world. Therefore, there is a need to develop effective antitumor agents that are targeted only to the specific site of the tumor to improve the efficiency of cancer diagnosis and treatment and, consequently, limit the unwanted systemic side effects currently obtained by the use of chemotherapeutic agents. In this context, due to its unique physical and chemical properties of graphene oxide (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…Moreover, stable and the reaching of high heat levels were proved (~79 • C) in comparison to the individual components (~33 • C) [71]. Romero et al (2021) functionalized the GO surface modified with PEG-folic acid, rhodamine B, and indocyanine green to treat Ehrlich tumors in mice by in vivo experiments using PDT and PTT with an NIR light of 808 nm 1.8 W/cm 2 . Based on fluorescence images of the tumor, the highest concentration of GO as a function of the time after intraperitoneal injection was determined [72].…”
Section: Application Of Go In Synergistic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, stable and the reaching of high heat levels were proved (~79 • C) in comparison to the individual components (~33 • C) [71]. Romero et al (2021) functionalized the GO surface modified with PEG-folic acid, rhodamine B, and indocyanine green to treat Ehrlich tumors in mice by in vivo experiments using PDT and PTT with an NIR light of 808 nm 1.8 W/cm 2 . Based on fluorescence images of the tumor, the highest concentration of GO as a function of the time after intraperitoneal injection was determined [72].…”
Section: Application Of Go In Synergistic Therapymentioning
confidence: 99%
“…Compared to PDT or PTT alone, the combined phototherapy managed to damage the tumor and diminish the tumor without return [132]. Romero et al (2021) designed theranostic nanocomposites based on GO with a surface modification of PEG-folic acid, rhodamine B, and indocyanine green (GO+RhodB, GO+PEGFA+RhodB, and GO+PEGFA+ICG). In addition to displaying red fluorescence spectra rhodamine B (as the fluorescent label), in vivo experiments were performed using GO to apply PDT and PTT in the treatment of Ehrlich tumors in mice using NIR light.…”
Section: Advantages Of Cbm In Pdt and Ptt Over Metal-organic And Organic Pssmentioning
confidence: 99%
“…Besides, stable and high heat reaching were proved (~79°C) in comparison to the individual components (~33°C) [69]. Romero et al (2021) functionalized GO surface modified with PEG-folic acid, rhodamine B, and indocyanine green to treat Ehrlich tumors in mice by in vivo experiments using PDT and PTT with a NIR light of 808 nm 1.8 W/cm 2 . Based on fluorescence images of the tumor, the highest concentration of GO as a function of the time after intraperitoneal injection was determined [70].…”
Section: Application Of Go In Synergistic Therapymentioning
confidence: 99%
“…Romero et al (2021) functionalized GO surface modified with PEG-folic acid, rhodamine B, and indocyanine green to treat Ehrlich tumors in mice by in vivo experiments using PDT and PTT with a NIR light of 808 nm 1.8 W/cm 2 . Based on fluorescence images of the tumor, the highest concentration of GO as a function of the time after intraperitoneal injection was determined [72].…”
Section: Application Of Go In Synergistic Therapymentioning
confidence: 99%
“…Tumor volume control showed that the GO+PEGFA+ICG group has the lower "R factor" ((V-Vo/Vo) normalized by day´s number of follow-up ) related to only the indocyanine group. Compared to PDT (only indocyanine PS) and PTT alone (only GO), the theranostic therapy diminish tumor without recurrence (see Figure 16) [72]. The PDT effect based on photoexcitation was studied, C-DOTs-PpIX showed more efficient cell killing ability than free PpIX as the cell viability of C-DOTs-PpIX group was much lower than that of the free PpIX group [133].…”
Section: Advantages Of Cbm In Pdt and Ptt Over Metal-organic And Organic Pssmentioning
confidence: 99%